2015
DOI: 10.1038/srep13262
|View full text |Cite
|
Sign up to set email alerts
|

CaMKII regulates the strength of the epithelial barrier

Abstract: Epithelial cells define the boundary between the outside and the inside of our body by constructing the diffusion barrier. Tight junctions (TJs) of epithelial cells function as barriers against invasion of harmful microorganisms into the human body and free diffusion of water or ions from the body. Therefore, formation of TJs has to be strictly controlled in epithelial cells. However, the molecular mechanisms governing this regulation are largely unknown. In this study, we identified Ca2+/calmodulin-dependent … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(24 citation statements)
references
References 32 publications
(38 reference statements)
0
24
0
Order By: Relevance
“…However, the CLDN1 C-terminal cytosolic tail presents several potential sites of posttranslational modification, including phosphorylation and ubiquitination, which may play a role in its trafficking (36). Indeed, other reports indicate a role for the phosphorylation of the CLDN1 cytosolic tail in the regulation of its subcellular localization in nonhepatic cells (37)(38)(39) or through a competition between phosphorylation and ubiquitination (40), as described for other members of the CLDN family (41,42). However, in our experimental work, the absence of the C terminus of CLDN1 did not alter the sensitivity of HCV infection to 5-HT6 and PKA antagonists, excluding a role for direct phosphorylation on CLDN1.…”
Section: Discussionmentioning
confidence: 99%
“…However, the CLDN1 C-terminal cytosolic tail presents several potential sites of posttranslational modification, including phosphorylation and ubiquitination, which may play a role in its trafficking (36). Indeed, other reports indicate a role for the phosphorylation of the CLDN1 cytosolic tail in the regulation of its subcellular localization in nonhepatic cells (37)(38)(39) or through a competition between phosphorylation and ubiquitination (40), as described for other members of the CLDN family (41,42). However, in our experimental work, the absence of the C terminus of CLDN1 did not alter the sensitivity of HCV infection to 5-HT6 and PKA antagonists, excluding a role for direct phosphorylation on CLDN1.…”
Section: Discussionmentioning
confidence: 99%
“…In support of a role for cldn1(T191) phosphorylation in enhancing junction localization, Shiomi et al 40 found that AMPK activation by AICAR resulted in phosphorylation of T191 in cldn1 and stimulated the formation of ectopic tight junction formation on lateral membrane of Eph4 cells; ectopic fibril formation is also seen with a phosphomimetic mutant of the analogous site in cldn3(T192) 37 and after cldn4 phosphorylation by protein kinase C epsilon. 36 Shiomi et al 40 further found that stimulated phosphorylation by AMPK activation was associated with decreased cldn1 ubiquitination at a nearby lysine (K189). These authors interpreted these findings to mean that cldn1 ubiquitination is normally required for turnover; blocking turnover by forced phosphorylation thus resulted in ectopic fibril formation.…”
Section: Other Cldn Phosphorylation Sites and Tight Junction Associationmentioning
confidence: 97%
“…31,[36][37][38][39][40][41] For example, phosphorylation of cldn1 (T191) 39 and cldn2(S208) 31 is associated with enhanced tight junction strand formation or localization; Fujii et al 39 found that hypotonic stress resulted in dephosphorylation at these sites and junctional removal by clathrin-dependent endocytosis. In support of a role for cldn1(T191) phosphorylation in enhancing junction localization, Shiomi et al 40 found that AMPK activation by AICAR resulted in phosphorylation of T191 in cldn1 and stimulated the formation of ectopic tight junction formation on lateral membrane of Eph4 cells; ectopic fibril formation is also seen with a phosphomimetic mutant of the analogous site in cldn3(T192) 37 and after cldn4 phosphorylation by protein kinase C epsilon. 36 Shiomi et al 40 further found that stimulated phosphorylation by AMPK activation was associated with decreased cldn1 ubiquitination at a nearby lysine (K189).…”
Section: Other Cldn Phosphorylation Sites and Tight Junction Associationmentioning
confidence: 99%
“…AMPK phosphorylates claudin 1 at Thr191 that promotes the formation of TJs in EpH4 breast cells. 81 In submandibular SMG-C6 cells, AMPK activation phosphorylates claudin 4 at Ser199 and further enhances claudin 4 and occludin interaction. 82 Cytoskeleton microtubules are critical for the maintenance of TJ structure and function.…”
Section: Ampk In Tight Junction Formation and Assemblymentioning
confidence: 99%